Waqf Asset Management For Water Facilities - Munifatussa'idah, Asma' (UIN Sunan Kudus, 2021)
The role of waqf in the social and economy of society has been proven by the increasing number of waqf practices in providing solutions for the welfare of Muslims. This research aims to explore the implementation of waqf asset management for in water facilities projects and waqf risk management in Badan Wakaf Al-Qur’an (BWA) Indonesia. This research uses a qualitative study with an explanatory approach, on a water facilities waqf project. The study uses primary data, through interviews with the program manager. The results show waqf asset management in the water facilities project in Muara Gembong, Bekasi, can be empowered productively by involving the role of the community as the manager of the waqf assets. Waqf asset management for water facilities consists of adjustment, assessment, planning, fundraising, realization, monitoring, and evaluation. The benefits of water facilities are intended for consumption purposes and to improve the beneficiary community’s economy.